Multicultural Value in the Traditional Islamic Boarding School, Bina Insan Mulia (BIMA), Cirebon, Indonesia - Eti Nurhayati; Yayah Nurhidayah (FITK UIN Walisongo, 2019)
Multicultural Education in Islamic Boarding Schools teaches tolerance and openness in carrying out activities of daily living. This research was conducted at the Bina Insan Mulia (BIMA) boarding school using descriptive qualitative methods, as well as data collection techniques by interviewing, observing, documenting studies, and FGDs. The conclusions of this study are: (1) The values of Multicultural Islamic Education implemented at the BIMA Islamic Boarding School are sourced from books / books taught to students / students such as the book of Hadith al-Arba'in Nawawiyah, Safinah al-Najah, Fath al-Qarib , Ta'lim al-Mutaa'llim, Taysir al-Khalaq, and Riyadh al-Saliheen; (2) The application of multicultural values includes openness, humanity, tolerance, mutual assistance, justice, equality, brotherhood. AbstrakPendidikan Multikultural di Pondok pesantren mengajarkan toleransi dan keterbukaan dalam melaksanakan aktifitas hidup sehari-hari. Penelitian ini dilakukan di pondok pesantren Bina Insan Mulia (BIMA) dengan menggunakan metode deskriptif kualitatif, serta teknik pengumpulan data dengan wawancara, observasi, studi dokumentasi, dan FGD. Kesimpulan penelitian ini adalah: (1) Nilai-nilai Pendidikan Islam Multikultural yang diterapkan di Pondok pesantren BIMA bersumber dari kitab / buku yang diajarkan kepada murid / Santri seperti kitab Hadits al-Arba'in Nawawiyah, Safinah al-Najah, Fath al-Qarib, Ta'lim al-Mutaa'llim, Taysir al-Khalaq, dan Riyadh al-Shalihin; (2) Penerapan nilai-nilai multikultural tersebut meliputi keterbukaan, kemanusiaan, toleransi, saling membantu, keadilan, kesetaraan, persaudaraan.